Αρμόδιος και Αριστογείτων: Μια διασκευασμένη τυρρανοκτονία στο ελληνικό προεπαναστατικό θέατρο - Chatzipanagioti-Sangmeister, Julia (The Gleaner, 2024)
Harmodius and Aristogeiton. An Adapted Tyrannicide in the Greek Pre-revolutionary Theater The tragedy Αρμόδιος και Αριστογείτων (Harmodius and Aristogeiton) is the most radical theatrical play performed by Greek amateur actors in Odessa in the years 1814-1820, since its subject is the tyrannicide as a legitimate resistance of citizens to power, when it arbitrarily abolishes natural law. The tragedy, first staged in 1819, was until now considered to be an original work of Georgios Lassanis (1793-1870), but my article proves that in fact it is a theatrical adaptation of a part of the novel Aristides und Themistocles (1792), written by the German scholar Ignaz Aurelius Feßler (1765-1839), a member of the Illuminati Order. A comparison of the novel with the ancient sources for the two tyrannicides shows that the changes made by the enthusiastic Kantian Feßler (mainly the concealment of the homoerotic character of the relationship between the two heroes) aimed to adapt the historical material to Kant’s conception that morality is based on the autonomy of the will. Lassanis kept the changes of Feßler and added some new inventions which emphasize even more the autonomy of the will as a condition of morality. The close relationship of Lassanis’ dramaturgy with his engagement as a member of the Filiki Etaireia becomes obvious not only in the choice of the subject of death for the homeland and democracy but is also manifest in his (pen-)name «Lyssanias». Lassanis’ nom de guerre is not a phonic variant of his name (as it has commonly been assumed until now) but rather refers to the verse of Aristophanes «Λυσανίαι πατρῴων μεγάλων κακῶν»; it therefore denotes one who liberates the homeland from sorrow and pain.